Form measurement and durability of mirror surfaces for concentrating solar power applications - King, Peter (Cranfield University, 2014)
Concentrating solar power systems currently have a high capital cost when compared with other energy generating systems. The solar energy is captured in the form of thermal energy rather than directly electrical, which is attractive as thermal energy is easier and currently cheaper to store in large amounts. It is also used directly as processing heat including desalination and water purification. For the technology to compete against other generating systems it is important to reduce the electrical energy cost to the $0.05 per kilowatt-hour level. One of the significant capital costs is the solar field, which contains the concentrators. To reduce the cost of this field, novel constructions and improvements to the durability and lifetime of the concentrators are required. Techniques for characterising the shape, durability and optical properties of such novel mirrors are the focus of this thesis. The thesis describes the development and validation of an inexpensive, highly portable photogrammetry technique, which has been used to measure the shape of large mirror facets for solar collectors. Photogrammetry has demonstrated its versatility and portability by successful measurements across concentrating solar power sites globally. The accuracy of the technique has been validated to show a measurement capability of better than 100 µm using a large coordinate measuring machine. Measurements performed on novel thin glass mirrors and their comparison with conventional thick glass mirrors are presented, showing that the increased flexibility of thin mirrors is an important consideration during installation, but that it is possible for such novel mirrors to perform to the same level. ...[cont.]